IABP: history-evolution-pathophysiology-indications: what we need to know. Issue 1 (December 2016) - Parissis, H.; Graham, V.; Lampridis, S.; Lau, M.; Hooks, G.; Mhandu, P.
Abstract Treatment with the intraaortic balloon pump (IABP) is the most common form of mechanical support for the failing heart. Augmentation of diastolic pressure during balloon inflation contributes to the coronary circulation and the presystolic deflation of the balloon reduces the resistance to systolic output. Consequently, the myocardial work is reduced. The overall effect of the IABP therapy is an increase in the myocardial oxygen supply/demand ratio and thus in endocardial viability. This is an overall synopsis of what we need to know regarding IABP. Furthermore, this review article attempts to systematically delineate the pathophysiology linked with the hemodynamic consequences of IABP therapy. The authors also look at the future of the use of the balloon pump and conclude that the positive multi-systemic hemodynamic regulation during IABP treatment should further justify its use.